Analysis of Differences in Levels of Financial Behavior towards Investment Preferences among Generation X and Generation Y in Urban Areas - Stephanie Bethania Pearly Simbolon; Harlyn L Siagian (Budapest International Research and Critics University, 2022)
The goal of this study was to see if there were any disparities in the amount of financial activity between men and women towards investment preferences between generation x and generation y in urban areas. The research methods used in this research are quantitative with comparative types. The respondents of the study used in this study were 60 respondents belonging to generation X and generation Y. The results of hypothesis testing using the t-test found that the t count value was -11,816 and the table value of df 59 was 2,000. So it is found that the value of t calculate is smaller than the value of the table t (-11,816 < 2,000). As a result, the null hypothesis was rejected and an alternate hypothesis was accepted. Based on the findings, it is possible to conclude that there is a difference in the level of financial behavior towards investment preferences between generation X and Generation Y in urban areas.